2013
DOI: 10.5664/jcsm.2576
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Advancement Splint as Short-Term Alternative Treatment in Patients with Obstructive Sleep Apnea Already Effectively Treated with Continuous Positive Airway Pressure

Abstract: MAS are now widely used for the treatment of OSA both as a primary therapy and as an alternative for patients with severe OSA who are unwilling or unable to tolerate CPAP. 5 MAS are a simple, reversible, quiet, and cost effective therapy for selected patients with OSA. study objectives: CPAP is used as the fi rst-line treatment for patients with severe OSA, but this machine is not always feasible to use on the long term. We performed a clinical trial to determine whether patients with OSA could use a mandibula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
12
1
Order By: Relevance
“…7 Moreover, studies suggest that patients who use oral appliances are often satisfied with their therapy. 8 These data support the use of oral appliances for those unable to tolerate positive airway pressure.…”
Section: Introductionmentioning
confidence: 72%
“…7 Moreover, studies suggest that patients who use oral appliances are often satisfied with their therapy. 8 These data support the use of oral appliances for those unable to tolerate positive airway pressure.…”
Section: Introductionmentioning
confidence: 72%
“…They reported that the residual AHI for MAD-treated patients was higher than a CPAP-treated group, but concluded that both CPAP and MAD may be effective therapies to reduce the risk of cardiovascular fatalities in patients with severe OSA. Although CPAP is regarded as the first option for patients with severe OSA, one study [23] investigated whether patients with severe OSA could use a MAD as an alternative treatment to CPAP. In that study, the AHI decreased with MAD use from 30.7 hr -1 to 13.2 hr -1 , and they concluded that MADs completely reduce sleep disordered breathing in selected patients with severe OSA.…”
Section: Discussionmentioning
confidence: 99%
“…OA should be considered not only an alternative to CPAP but rather a potentially complementary treatment modality to further improve treatment outcomes. The combination of OA and CPAP to be used on alternative days has been reported as a successful approach . Almeida et al found that patients who were compliant with CPAP (>4 h/night) had their sleepiness further improved once they had the option to use an OA when CPAP was not being worn.…”
Section: Oral Appliancementioning
confidence: 99%
“…The combination of OA and CPAP to be used on alternative days has been reported as a successful approach. 46 Almeida et al found that patients who were compliant with CPAP (>4 h/night) had their sleepiness further improved once they had the option to use an OA when CPAP was not being worn. Patients did describe a smaller burden of this therapy, having an option for a day off CPAP, and also described less pressure on teeth, having a day off OA.…”
Section: Oral Appliancementioning
confidence: 99%